2001
DOI: 10.1139/cjpp-79-8-705
|View full text |Cite
|
Sign up to set email alerts
|

The physiological and pathophysiological modulation of the endocrine function of the heart

Abstract: Under physiological conditions, the endocrine heart contributes to the maintenance of cardiovascular homeostasis through the polypeptide hormones ANF and BNP, which are members of the natriuretic peptide (NP) family. Given that NPs are of interest from the basic and clinical points of view, the genetic expression and secretion of ANF and BNP as well as the nature of the interaction of these hormones with their receptors has been the subject of extensive studies since the discovery of ANF in 1980. Following hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 53 publications
0
51
0
3
Order By: Relevance
“…This indicates that serum ANP might predominantly have extracardiac functions. The increase in ANP 6 h after load might be explained by the release of stored ANP in the granula of the atrial myocytes [6]. Reason for the lack of systemic ANP on myocardial SERCA regulation could be the higher degradation of ANP in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that serum ANP might predominantly have extracardiac functions. The increase in ANP 6 h after load might be explained by the release of stored ANP in the granula of the atrial myocytes [6]. Reason for the lack of systemic ANP on myocardial SERCA regulation could be the higher degradation of ANP in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the agonists of cNPs secretion, such as ET1, angiotensin II (AII) and PE, signal through the receptors coupled to Gq proteins, although other subclasses may also be used (42, 43) and stimulate the RAS/c-Raf-1 and the phosphoinositide signalling pathways leading to the recruitment and activation of effector molecules such as those found in MAP kinase cascades (44, 45). Gi/o inhibition by pertussis toxin (PTX) abolishes stretch-secretion coupling without affecting baseline secretion through a mechanism that is independent of Gq signalling, suggesting that PTX sensitive Gi/o proteins are involved in stretch-induced secretion in atria.…”
Section: The Natriuretic Peptide Family (Anf Bnp and Cnp)mentioning
confidence: 99%
“…The advent of the more sensitive radioimmunoassay techniques to measure these NPs revealed that they were also present in ventricular muscle albeit at much lower concentrations than in the atria. Transcript abundance reflects this difference [5, 10, 11]. In addition, in both atria and ventricles, ANF is always more abundant than BNP [12, 13].…”
Section: Introductionmentioning
confidence: 99%